INSTITUTIONAL REPOSITORY AS A DIGITAL LITERACY ACCESS (International Conference on Social and Islamic Studies, 2022)
The existence of the internet has changed the paradigm of thinking and acting of its users. Paradigm, which was not as complex as in this era, is now expanding into paradigm expansion and action. The repository as a platform for scientific communication or as digital literacy has begun to be used in universities in Indonesia. The massive amount of information circulating on the internet is the beginning of awareness of the importance of knowing a valid database as a form of the role of the repository institution as a forum for digital literacy. However, there are still many students and stakeholders who do not know and understand the existence of repository institutions as an answer to their anxiety in working on scientific papers. The aim of this research is to find out the role of the repository as a means of digital literacy. The research method uses Edmund Husserl's classical phenomenology which emphasizes human awareness using a qualitative approach.  The findings are repository institutions as a forum for digital literacy. Exchanging information is important in spreading the existence of this database so that this database can be optimized for use. Implication: The implication of this research is that the existence of this digital platform increases the literacy of the stakeholders concerned in digital access as a means of scientific communication both as users and as workers behind the repository institution.